THE MODERN TECHNIQUES OF TEACHING VOCABULARY IN EFL CLASSES - Botirova , Z.X; Ahmedova , Mahliyo Bahodirjon qizi (Educational Research in Universal Sciences, 2023)
This article explores modern techniques for teaching vocabulary in EFL (English as a Foreign Language) classes. It discusses various methods, their results, and their implications for language learners. The aim is to provide educators with effective strategies to enhance vocabulary acquisition among EFL students.